2019
DOI: 10.1109/tmtt.2019.2919509
|View full text |Cite
|
Sign up to set email alerts
|

Peak and Average Power Handling Capability of Microstrip Filters

Abstract: In this work, the power handling capability of microstrip filters is studied in detail. This study is addressed from two perspectives, depending on the physical phenomenon limiting the maximum power that the microstrip filter can handle. One of these phenomena is air breakdown or corona effect, which is linked to the peak power handling capability (PPHC) of the device, and the other is the self-heating, which limits the device average power handling capability (APHC). The analysis is focused on three kinds of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 23 publications
(29 reference statements)
2
23
0
3
Order By: Relevance
“…From the measured data of Fig. 14, one can see that, as expected, the obtained power thresholds are higher than simulations in SPARK3D ® (see [13]), mainly for the increase of the insertion losses with regard to the simulated frequency response. As we can see in Fig.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…From the measured data of Fig. 14, one can see that, as expected, the obtained power thresholds are higher than simulations in SPARK3D ® (see [13]), mainly for the increase of the insertion losses with regard to the simulated frequency response. As we can see in Fig.…”
Section: Resultssupporting
confidence: 70%
“…9(d), there are not covers in the fifth resonator. For the five-pole filter, simulations with SPARK3D ® have shown that first, second, third, and fourth resonators have the possibilities to generate corona breakdown at center and/or critical frequencies, due to their higher voltage magnification (see [13]). This does not occur in the fifth resonator, where the stored energy is the lowest one (see [6]), thus, the use of covers can be avoided in this resonator.…”
Section: Simulated Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, in microstrip circuits, the study of corona discharge has been mainly focused on the connectors feeding microstrip transmission lines [10]- [12]. Recently, some investigations have analyzed the maximum peak voltage and PPHC of microstrip coupled-line filters [13]. In this context, therefore, the main aim of this paper is to contribute to the state-of-the-art by proposing a modified microstrip filter structure with improved power handling capability.…”
Section: Introductionmentioning
confidence: 99%